Development of Smart Mouse Trap Model - Mohd Salleh, Nor Hamizah Syazwani; ABDULLAH, NURHANIM SAADAH (Research and Innovation in Technical and Vocational Education and Training, 2022)
Pests such as mice give so much trouble to human beings. This is because the mouse is known as the disease agent. Moreover, they can spread diseases such as Leptospirosis, Lymphocytic Choriomeningitis Virus (LCMV), and Hantavirus through their saliva and urine. It is most risky when the mouse also shares the same habitat with human beings such as homes, offices, and warehouses. Hence, the Development of the Smart Mouse Trap Model functions to solve human being’s problems with the mouse at their homes, offices, and warehouses. The main objective of this study is to design the Smart Mouse Trap Model. This model equipped with motion-sensing for interacting with emitting infrared light, to develop the Smart Mouse Trap Model with the motion-sensing features, and to test the functionality. This study was developed by using the Waterfall Model which involves seven phases consists Requirement Phase, Analyze Phase, Design Phase, Coding Phase, Testing Phase, Operation Phase, and Maintenance Phase. The Smart Mouse Trap Model successfully detects the motion by using the Passive Infrared (PIR) Sensor and sends the data to the Blynk to notify the user about the amount of the mouse in the trap. This study involves the use of technology electronic components such as WiFi Module NodeMCU ESP32, Passive Infrared (PIR) Sensor, and Liquid Crystal Display (LCD). The development of the Smart Mouse Trap Model might help to reduce the rate of patients who are suffering from zoonotic diseases such as Leptospirosis, and Hantavirus